Preparation of Freeze-Dried Porous Chitosan Microspheres for the Removal of Hexavalent Chromium - Wei Song; Jian Xu; Lepeng Gao; Qingzhu Zhang; Jin Tong; Lili Ren (Applied Sciences, 2021)
Novel porous chitosan microspheres were successfully produced by a freezing–lyophilization drying method in this study and were then used as adsorbents to remove a toxic iron metal, hexavalent chromium (Cr(VI)). The effects of the concentration of the chitosan solution, syringe diameter, and freezing time on the morphologies of porous chitosan microspheres were characterized. The metal ion adsorption for Cr(VI) was also studied. Results showed that freezing chitosan hydrogel beads at a temperature of −20 °C and subsequently lyophilizing the frozen structure allowed to easily obtain the porous chitosan microspheres with rough surfaces and large pores, which were more suitable for adsorption materials to remove metal ions. A chitosan solution concentration of 3% (w/v) and a syringe diameter of 500 μm allowed the porous microspheres to have a good sphericity, thinner pore walls, and small pore sizes. The adsorption capacity of porous chitosan microspheres for Cr(VI) increased with the increase in freezing time. The pH of the initial adsorption solution ranged from 3.0 to 5.0 and was beneficial to the maximum adsorption efficiency for Cr(VI). The porous chitosan microspheres prepared with 3% (w/v) chitosan solution at −20 °C for a freezing time of 72 h had a higher adsorption capacity of 945.2 mg/g for Cr(VI) than the those at 24-h and 48-h freezing times. Kinetic study showed that the adsorption process could be described by a pseudo-second order (PSO) kinetic model. The equilibrium adsorption rate constant and the adsorption amount at equilibrium for the porous chitosan microspheres increased with an increase in the freezing time, and those for the porous microspheres prepared with 3% chitosan solution at −20 °C for a 72-h freezing time were 1.83 × 10−5 g mg−1 min−1 and 1070.5 mg g−1, respectively. The porous chitosan microspheres have good potential to facilitate the separation and recycling of expensive and toxic Cr(VI) from wastewater.